Aplicación de procesos y políticas de la informática forense en las seguridades de servidores. Caso práctico servidor B-Learning de la Universidad Nacional de Chomborazo. - Fierro Zúñiga, Fredy Alejandro (2013)
The following work aims to determine the importance that forensic informatics has to identify strengths and weakness into the B-learning system of the Chimborazo National University. Once done, it could help to make a follow up to this process in order to apply and also improve the parameters of this service. During the analysis, some features of investigation were pointed out. After that, it was applied MAGERIT methodology, which allows identifying the mains aspects to take into consideration for protect those informatics services that the University gives to their students. A special emphasis was made into those services with more expanded use, monitoring them, so it could be detected possibilities of failures and avoiding future risks.